A GPI Signal Peptide-Anchored Split-Ubiquitin (GPS) System for Detecting Soluble Bait Protein Interactions at the Membrane. Issue 1 (23rd July 2018) - Zhang, Ben; Karnik, Rucha; Donald, Naomi; Blatt, Michael R.
Abstract : Bait fusion proteins with a glycosyl-phosphatidylinositol signal sequence anchor enable effective split ubiquitin screening for interactions with otherwise soluble membrane proteins.